On the Application of Diffusion Models for Simultaneous Denoising and Dereverberation - Meise, Adrian Tobias; Cord-Landwehr, Tobias; Haeb-Umbach, Reinhold (ITG Conference on Speech Communication)

Probing Metal Tip‐Induced Bond Weakening of a Reactive Alkyne Center Aligned via a Rigid Triphenylmethane‐Based Tripod on Au(111) by TERS and DFT - Li, Gang; Mennicken, Simon; Zhu, Lu‐Yao; Ehtesabi, Sadaf; Reichenauer, Till; Kupfer, Stephan; Schäfer, Daniel; Mehrparvar, Saber; Haberhauer, Gebhard; Zhang, Yao; Gräfe, Stefanie; Schlücker, Sebastian; et al. (Journal of Raman Spectroscopy)
ABSTRACT The chemical reactivity of molecules can be controlled by a variety of effects, ranging from chemical reagents to purely physical stimuli. Metal tips employed in scanning probe microscopy are an elegant tool to manipulate reactive centers in single molecules. However, to achieve excellent control over distance and orientation, it is crucial to immobilize the reactive center and align it along the direction of the tip. Here, we aligned a reactive alkyne center via a rigid triphenylmethane‐based tripod for upright adsorption on Au(111) for inducing bond weakening in the alkyne moiety by approaching a silver tip. Single‐molecule ultrahigh vacuum low‐temperature tip‐enhanced Raman scattering was employed for probing tip‐induced bond weakening in the gap distance range from 550 to 250 pm. Both the ≡C–H stretching at ~3330 cm −1 and the dominant –C≡C– stretching peak at ~2130 cm −1 exhibit a shift to smaller wavenumbers due to tip‐induced bond weakening and an exponential increase in Raman intensity originating from the increased local electric field in the nanogap. To rationalize the underlying physical contributions and chemical effects of tip‐induced bond weakening, density functional theory calculations for gap distances in the range 800 to 100 pm were performed. The computational results confirmed the presence of different gap distance regimes including the onset of Pauli repulsion for short distances; for the latter, the calculations additionally predict structural distortions of the terminal alkyne induced by the nearby metal tip. These findings allow us to set a lower limit for the tip–tripod gap distance in studies requiring an intact upright configuration of the alkyne‐tripod, for example, electric field‐induced chemistry.

Creep Effects of Thermoplastic Flange Systems - Bartmann, Finn; Riedl, Alexander; Moritzer, Elmar (Lecture Notes in Mechanical Engineering)

Atmosphärendruckplasma: Grenzflächenmodifikation von Werkzeugstahl: Plasma trifft Stahl: Möglichkeiten zur Modifikation und Verbesserung von Oberflächeneigenschaften - Moritzer, Elmar; Rauen, Dennis; Hoppe, Justin (Magazin für Oberflächentechnik)
Keywords: Plasma; Plasmaaktivierung; Werkzeugstahl

A COMPARISON OF USING FILM INSTEAD OF POLYMER POWDER FOR POLYPROPYLENE GLASS-FIBER COMPOSITE LAMINATES - Moritzer, Elmar; Brandes, Philipp; Wittler, Maurice; Westphal, Max Siegfried (Annual Technical Conference of the Society of Plastics Engineers (ANTEC 2025))
Keywords: Faser-Kunststoff-Verbunde (FKV); Faserverstärkte Kunststoffe (FVK); Organobleche

Untersuchung des Erwärmverhaltens von Organoblechen mittels IR-Strahlung für das Fügen im Stempelnietverfahren - Moritzer, Elmar; Völklein, Paul Leonhard (Technomer 2025 29. Fachtagung)
Keywords: Faserverstärkte Kunststoffe (FVK); mechanischens Fügen; Nieten; Organobleche

Ambossfreies Ultraschallschweißen für nur einseitig zugängliche Schweißsituationen - Arndt, Theresa; Schöppner, Volker (Joining Plastics)
Keywords: Schweißen; Ultraschall; weld seam quality

Berücksichtigung des Kriechverhaltens bei numerischen Simulationen von Thermoplastflanschverbindungen - Moritzer, Elmar; Bartmann, Finn; Riedl, Alexander (1. XXIV Dichtungskolloquium (Essen Juni 2025))
Externer Doktorand von Moritzer

Förderung der sozial-emotionalen Kompetenzen von Kindern im Zusammenhang mit dem kooperativen Lernen im diversitätssensiblen Grundschulunterricht (soko-M). Vortrag auf der Herbsttagung 2025 der Arbeitsgruppe Empirische Sonderpädagogische Forschung (AESF). - Klostermeier, Jasmin; Knickenberg, Margarita; Löper, Marwin Felix; Grosche, Michael; Grüßing, Meike; Hellmich, Frank

PROCESS DEVELOPMENT OF A POWDER-BASED DIRECT COATING IN THE INJECTION MOLDING PROCESS - Moritzer, Elmar; Lingnau, Kai (Annual Technical Conference of the Society of Plastics Engineers (ANTEC 2025))
Keywords: Lackierung; Pulverlack; Spritzgießen

Prädiktoren für die Selbstwirksamkeitsüberzeugungen von angehenden Lehrkräften im Zusammenhang mit der Gestaltung inklusiven Unterrichts. - Görel, Gamze; Franzen, Katja; Hellmich, Frank (Zeitschrift für Entwicklungspsychologie und Pädagogische Psychologie)

Effects of a social participation intervention on primary school students’ attitudes toward peers with disabilities (accepted) - Löper, Marwin Felix; Hassani, Sepideh; Görel, Gamze; Schwab, Susanne; Hellmich, Frank (Journal of Research in Special Educational Needs)

Safe Continual Learning in Model Predictive Control With Prescribed Bounds on the Tracking Error - Lanza, Lukas; Dennstädt, Dario; Berger, Thomas; Worthmann, Karl (International Journal of Robust and Nonlinear Control)
ABSTRACT We develop a three‐component Model Predictive Control (MPC) algorithm to achieve output‐reference tracking with prescribed performance for continuous‐time nonlinear systems. One component is the so‐called funnel MPC, which achieves reference tracking with prescribed performance for the model output for suitable models. Recently, this MPC algorithm has been combined with a model‐free reactive feedback controller (second component) to account for model‐plant mismatches, bounded disturbances, and uncertainties. By construction, this two‐component controller defines a robust funnel MPC algorithm. It achieves output‐reference tracking within prescribed bounds on the tracking error for a class of unknown nonlinear systems. In this paper, we extend the robust funnel MPC by a machine learning component to adapt the underlying model to the system data and, thus, improve the contribution of MPC. We derive sufficient structural conditions to define a class of models for funnel MPC, and provide a characterization of suitable learning schemes. Since robust funnel MPC is inherently robust and the evolution of the tracking error in the prescribed performance funnel is guaranteed, the additional learning component can perform the learning task online—even without an initial model or offline training.

On Model Predictive Funnel Control With Equilibrium Endpoint Constraints - Göbel, Jens; Dennstädt, Dario; Lanza, Lukas; Worthmann, Karl; Berger, Thomas; Damm, Tobias (IEEE Control Systems Letters)

A Model-Free Approach to Control Barrier Functions Using Funnel Control - Lanza, Lukas; Köhler, Johannes; Dennstädt, Dario; Berger, Thomas; Worthmann, Karl (IEEE Control Systems Letters)

A low-complexity funnel control approach for non-linear systems of higher-order - Dennstädt, Dario (IFAC-PapersOnLine)

Funnel control with input filter for nonlinear systems of relative degree two - Dennstädt, Dario; Schaa, J.; Berger, T. (arXiv:2512.17806)
We address the problem of output reference tracking for unknown nonlinear multi-input, multi-output systems with relative degree two and bounded-input bounded-state (BIBS) stable internal dynamics. We propose a novel model-free adaptive controller that ensures the evolution of the tracking error within prescribed performance funnel boundaries. By applying an output filter, the control objective is achieved without utilizing derivative information of system's output. The controller is illustrated by a numerical example.

Sustainable design and repair: Leveraging circular economy and machine learning for product development - Mohammadian, Noushin; Fatahi Valilai, Omid; Schlüter, Alexander (Journal of Open Innovation: Technology, Market, and Complexity)

Development of an AI-driven decentralized control for fifth generation district heating and cooling networks - Donner, Johannes Aurelius Tamino; Schlüter, Alexander (SDEWES Conference 2025)
Keywords: 5GDHC; district heating; DHC; waste heat; AI-Driven

Universitäre Lehre in der Produktentwicklung/Academic teaching in product development - Bender, Beate; Husung, Stephan; Kirchner, Eckhard; Kletzin, Ulf; Kossack, Frederike; Lohrengel, Armin; Magyar, Balázs; Riedel, Oliver; Stahl, Karsten (Konstruktion)
Inhalt Der Leitfaden der Wissenschaftlichen Gesellschaft für Produktentwicklung (WiGeP) dient als umfassende Orientierung für die Gestaltung der universitären Lehre im Bereich der Produktentwicklung. Er wurde überarbeitet, um aktuellen gesellschaftlichen Herausforderungen wie dem Klimawandel, sinkenden Studierendenzahlen und abnehmenden technischen Vorkenntnissen zu begegnen. Ein zentrales Anliegen ist es, Ingenieurinnen und Ingenieure zu befähigen, aktiv zur Lösung globaler Probleme beizutragen. Didaktisch wird der Einsatz moderner Lehrmethoden wie Projektarbeit, Flipped-Classroom, digitale Tools, VR-Lernen sowie adäquater Prüfungsformate nach Taxonomiestufen empfohlen. Inhaltlich stehen Maschinenelemente, methodische und virtuelle Produktentwicklung im Fokus, ergänzt durch interdisziplinäre Themen wie Nachhaltigkeit, Digitalisierung und Technikethik. Zudem wird die Bedeutung technischer Bildung an allgemeinbildenden Schulen hervorgehoben, um die Studierfähigkeit und Begeisterung für Technik frühzeitig zu fördern. Der Leitfaden richtet sich an Lehrende an Hochschulen, Hochschuldidaktiker, Studiengangverantwortliche sowie bildungspolitische Entscheidungsträger und interessierte Akteure aus Gesellschaft und Industrie. Insgesamt versteht sich der Leitfaden als strategisches und operatives Werkzeug zur Weiterentwicklung der ingenieurwissenschaftlichen Lehre mit dem Ziel, exzellent ausgebildete und gesellschaftlich verantwortungsbewusste Produktentwicklerinnen und Produktentwickler für die Zukunft zu qualifizieren.